Key astroglial markers in human liver cirrhosis of different degree: immunohistochemical study - Shulyatnikova, T. V.; Tumanskyi, V. O.; Шулятнікова, Тетяна Володимирівна; Туманський, Валерій Олексійович (Запорізький державний медичний університет, 2022)
The aim of the study – determining the immunohistochemical levels of the GFAP, GS and AQP4 in different regions of the human brain in the conditions of liver cirrhosis of different degree. Materials and methods. The study was performed on sectional material of 90 patients who suffered during lifetime from liver non-alcoholic cirrhosis of classes A (n = 30, group “A”), B (n = 30, group “B”) and C (n = 30, group “C”) according to Child–Pugh classification, including 59 (65.55 %) cases with clinical symptoms of I–IV grade hepatic encephalopathy. Cortex, white matter, hippocampus, thalamus, striopallidum, cerebellum, were examined using immunohistochemical method for evaluation of GFAP, GS and AQP4 levels. Results. GFAP expression gradually decreased from classes A to C of cirrhosis. The most expressed GFAP decline was found in class C in the cortex and thalamus (6.74- and 6.23-fold decrease). Contrary to GFAP, GS expression gradually increased along with aggravation of cirrhosis. The most prominent augmentation of GS was related in the cortex and thalamus in “C” group, respectively 4.34- and 4.26-fold increase. AQP4 levels also showed growing mode correlated with cirrhosis aggravation. The highest increase was found in the cortex and thalamus in “C” group (4.25- and 4.34-fold increase, respectively). Starting from class B, altered GFAP, GS, and AQP4 levels showed region-dependent relationships. GS and AQP4 were positively correlated in all 6 studied regions, while the inverse relationships were found between GFAP vs. GS and GFAP vs. AQP4 proteins. Мета роботи – визначення імуногістохімічних рівнів GFAP, GS та AQP4 у різних ділянках головного мозку людини за умов цирозу печінки різних ступенів тяжкості. Матеріали та методи. Дослідження здійснили на секційному матеріалі 90 пацієнтів, які протягом життя хворіли на неалкогольний цироз печінки класів А (n = 30, група «А»), В (n = 30, група «В») та С (n = 30, група «С») за класифікацією Чайлд–П’ю, у тому числі 59 (65,55 %) випадків із клінічною симптоматикою печінкової енцефалопатії I–IV ступенів. За допомогою імуногістохімічного методу досліджували кору, білу речовину, гіпокамп, таламус, стріо-палідум і мозочок для оцінювання рівнів GFAP, GS та AQP4. Результати. Експресія GFAP поступово знижувалася, починаючи з цирозу класу А, набула найменших значень у корі та таламусі хворих класу С (зменшення у 6,74 і 6,23 раза). На відміну від GFAP, експресія GS поступово зростала разом з обтяженням цирозу. Найвиразніше підвищення GS виявили в корі, таламусі в групі «С» (у 4,34 і 4,26 раза відповідно). Рівні AQP4, що зростали, також корелювали з підвищенням класу цирозу. Найбільший приріст виявили в корі, таламусі в групі «С» (підвищення в 4,25 і 4,34 раза). Починаючи з класу B, у змінах експресії GFAP, GS і AQP4 встановили регіон-залежні кореляційні зв’язки. GS і AQP4 позитивно корелюють між собою в усіх 6 регіонах, що дослідили, а між білками GFAP/GS, GFAP/AQP4 виявили зворотний зв’язок.
Ключові маркери астроглії при цирозі печінки різних ступенів тяжкості у людини: імуногістохімічне дослідження
Shulyatnikova T. V. - ID: 0000-0002-0196-9935; Tumanskyi V. O. - ORCID ID: 0000-0001-8267-2350.
Keywords: liver cirrhosis; astroglia; reactivity; GFAP; GS; AQP4; hepatic encephalopathy; immunohistochemistry; цироз печінки; астрогліальна реактивність; печінкова енцефалопатія; імуногістохімія